PLATELET DISTRIBUTION WIDTH VALUE AS A DIAGNOSTIC AND PROGNOSTIC MARKER IN ACUTE CORONARY SYNDROME - Rahmi Rifany Latif; Liong Boy Kurniawan; Darmawati Rauf (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
An acute coronary syndrome is a form of clinical manifestation of coronary heart disease with atherosclerosis, and thrombosis processes. Platelets play an essential role in thrombosis. High PDW shows a variation of the morphology, and size of a platelet. This was a retrospective cross-sectional study comparing PDW, length of stay, and patient outcome in STEMI, NSTEMI, UAP, and control patients at the Dr.Wahidin Sudirohusodo Hospital Makassar during the period of January 2014 – December 2015. Data were analyzed using statistical software. One hundred, and seventy-two ACS patients were included; 65 patients had UAP, 48 patients had STEMI and 59 patients had NSTEMI. Sixty normal patients were included as a control. Kruskal-Wallis test showed a statistical difference in PDW between patients with STEMI, NSTEMI, UAP, and control (p=0.000). Post hoc test showed a significant difference between ACS, and control, STEMI, and control (p=0.000), NSTEMI and control (p=0.000), UAP, and control (p=0.000), but there no significant difference     between STEMI, and NSTEMI (p=0.320), STEMI, and UAP (p=0.980), NSTEMI and UAP (p=0.435). There was no significant difference in PDW between patients who survived, and died (p=0.298), and also patients with a length of stay of ≤ 7 days, and > 7 days (p=0.293). Platelet distribution width was higher in ACS patients compared with control patients, but could not be used to predict the outcome, and length of stay of patients with ACS. It is advisable to do further research with a large sample size to avoid bias.